THE LINGUISTIC CHOICE BY INDONESIAN-SPEAKING ADOLESCENTS: A CASE STUDY IN TANGERANG - Bernadette Kushartanti (Masyarakat Linguistik Indonesia, 2020)
This study presents a result of a survey on linguistic choice by adolescents who live in Tangerang, a neighboring area of Jakarta. In this study, we observed their use of Bahasa Indonesia (BI), Colloquial Jakarta Indonesian (CJI), foreign language (FL), regional language (RL), and mixed language (ML) in interactions with different addresees in daily activities: parents, teachers, friends, siblings, grandparents, uncles/aunts, and new acquaintances. Data in this study were collected from questionnaires, distributed at two secondary schools (SMP) and two senior high schools—a sekolah menengah umum ‘general senior high school’(SMU) and a sekolah menengah kejuruan (SMK) ‘vocational senior high school’ (SMK) which are located in Tangerang. The participants in this study are the students, aged 13 to 19 years old (N=748). It is found that BI and CJI were frequently used by these teenagers. They tended to use BI in interactions—spoken and written—with the older and respected people (teachers, parents, and grandparents) or those who are not familiar with them. CJI is used to those who are socially equal to them. Some of them used ML. Only a few of these participants use RL, and very few use FL. This study also finds that there are differences on the pattern between the use of BI and CJI in spoken and written interactions. Another factor that makes the difference between these varieties is the educational level. Findings in this study indicates that these languages—especially BI and CJI—have functions respectively, and the respondents’s choice is strongly influenced by the status of the participants and social contexts.